A repercussão geral no recurso extraordinário: breves considerações sobre o tema - Paes, Flávia Correa (2008)
The present work has the aim to understand the institute of General Repercussion, from the systematization of various historical, conceptual and practical aspects that are able to illustrate an important convergency of these factors that contributed to the alignment precipuous purpose of the Federal Supreme Court, from an essential Constitutional Court. The study of this requirement which has arisen together with the Constitutional 2004 Reform for appeals to the Supreme Court which consists of showing the relevance as well as transcendency in the subject focused herein. Such studies are justified due to the importance of the subject regarding the profound alteration in a constitutional environment and the legal and regimental changes over them, and how the whole set of bylaws reflected in the Federal Supreme Court as well as in the extraordinary Law System. As to understand these alterations, firstly, we have to analyze the historical and conceptual aspects in foreign law. Thus, we move on to the analysis of a similar institution of remedy qualification named Relevance Allegement which has in full force between 1975 and 1988 in the Brazilian Law System. Going through the necessary historical events, the institute of General Repercussion starts being analysed, clarifying the vague concept. At least, the procedimental issue is shown from the legislation and update of the subject concerning the Federal Supreme Court